Subtle Alterations in DNA Methylation Patterns in Normal Cells in Response to Dietary Stilbenoids. Issue 14 (26th June 2018) - Beetch, Megan; Lubecka, Katarzyna; Kristofzski, Heather; Suderman, Matthew; Stefanska, Barbara
Abstract : Scope: Searching for correlations between dietary polyphenols and risk of chronic diseases has been a challenge due to the lack of quantitative evaluation methods of long‐term exposure. We previously observed substantial DNA methylation changes in human cancer cells upon treatment with polyphenols of the stilbenoid class. When induced in normal cells, such molecular changes may persist and reflect chronic exposure. Methods and results: Illumina 450K microarray is used to delineate a genome wide DNA methylation landscape in MCF10A human immortalized mammary epithelial cells exposed to resveratrol (RSV) at noncytotoxic 15 μM dose for 9 days. Subtle alterations are observed suggesting remodeling of DNA methylation patterns rather than switch on/off changes. Using pyrosequencing, DNA methylation is quantitatively measured at eight CpG sites located within KCNJ4, RNF169, BCHE, DAOA, HOXA9, RUNX3, KRTAP2‐1, and TAGAP, upon exposure to RSV or pterostilbene and shows similar differences induced by both stilbenoids. Two of the probes, Runx3 and Kcnj4, are successfully verified in whole blood DNA from healthy rats on diets supplemented with stilbenoids. Conclusions: The study provides strong support for testing the utility of polyphenol‐mediated changes in DNA methylation as quantitative measures of long‐term dietary exposures in nutritional epidemiology and clinical trials. Abstract : Subtle alterations in DNA methylation are detected in normal cells exposed to polyphenols of the stilbenoid class, such as resveratrol or pterostilbene, and in whole blood of rats whose diets were supplemented with the compounds. Once confirmed in population‐based studies, such molecular markers can be used as an excellent tool to reliably measure long‐term polyphenol exposure and establish associations between polyphenol intake and risk of chronic diseases.